(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
André Carreira (1960) inaugurated great relevant practices and theories for latin american theater. In this dialogue, the director talks about the beginning of his career and the main artistic influences that permeate his history. Furthermore, he gives clues to the concept of the city and the notion of urban space as dramaturgy and clarifies his understanding about the terms conventional and unconventional spaces, theater in the city, theater in the street, street theater, among others. The semi-structured interview was divided into three parts: the first deals with general aspects about theatrical forms and urban space; the second emphasizes theater on the street, and the third exposes the experience with the Teatro que Roda – Theater that Runs – group (Goiânia/Goiás/Brazil). The opportunity for the meeting was held in person, in 2014, at the time the interviewee was participating in a project in the city of Goiânia. Carreira had access to the raw transcript of the material, which he also reviewed prior to publication.